Correlation of humoral immune responses to different SARS-CoV-2 antigens with virus neutralizing antibodies and symptomatic severity in a German COVID-19 cohort. Issue 1 (1st January 2021) - Rockstroh, Alexandra; Wolf, Johannes; Fertey, Jasmin; Kalbitz, Sven; Schroth, Stefanie; Lübbert, Christoph; Ulbert, Sebastian; Borte, Stephan
ABSTRACT: Monitoring the humoral protective immune response and its durability after SARS-CoV-2 infections is essential for risk assessment of reinfections, the improvement of diagnostic methods and the evaluation of vaccine trials. We have analyzed neutralizing antibodies and IgG responses specific to different antigens, including the inactivated whole-virion of SARS-CoV-2, the spike subunit 1 protein and its receptor binding domain, as well as the nucleocapsid protein. We show the dynamic developments of the responses from the early convalescent stages up to 9 months post symptoms onset in follow-up samples from 57 COVID-19 patients with varying clinical severity. By correlating antibody signals to neutralizing titres, valid diagnostic markers for the estimation of neutralizing protection could be identified.